Mysterious long noncoding RNAs and their relationships to human disease - Li, Wenchao; Wang, Yang Yang; Xiao, Lifei; Ding, Jiangwei; Wang, Lei; Wang, Feng; Sun, Tao (Frontiers in Molecular Biosciences, 2022)
Increasing studies have shown that the formation mechanism of many human diseases is very complex, which is determined by environmental factors and genetic factors rather than fully following Mendel's genetic law of inheritance. Long non-coding RNA (lncRNA) is a class of endogenous non-protein coding RNA with a length greater than 200nt, which has attracted much attention in recent years. Studies have shown that lncRNAs have a wide range of biological functions, such as roles in gene imprinting, cell cycle progression, apoptosis, senescence, cell differentiation, and stress responses, and that they regulate the life processes of mammals at various levels, such as epigenetic transcription, processing, modification, transport, translation and degradation. Analyzing the characteristics of lncRNAs and revealing their internal roles can not only deepen our understanding of human physiological and pathological processes, but also provide new ideas and solutions for the diagnosis, prevention and treatment of some diseases. This article mainly reviews the biological characteristics of lncRNAs and their relationship with diseases, so as to provide references for the related research of lncRNAs.